Comfort of the urban environment of Penza as assessed by student youth - N.V. Korzh; V.N. Supikov (Известия высших учебных заведений. Поволжский регион: Общественные науки)
Background. Modern urban agglomerations are becoming centers of education, production, trade, provision of services, leisure, etc. Depending on the quality and comfort of the urban infrastructure, the attitude towards this settlement is formed both by local residents and tourists. Young people are active users of the infrastructure facilities of the urban environment. If the city does not allow young people to fully realize themselves, they leave it. The purpose of this work is to study the parameters of the comfort of the urban environment of Penza for modern student youth. Materials and methods. To achieve this goal, the results of the authorʼs study conducted among student youth in 2024 were used. In addition, data from all-Russian surveys presented by VTSIOM were used. Results. The study revealed the understanding of the “comfortability of the urban environment” among young people, identified the difficulties that young people face in their city, and characterized the leisure of young people. Conclusions. The study revealed ambiguous assessments of the comfort of the urban environment of Penza from student youth. Young people highlighted both the positive aspects of living in their city and focused on the problems. The results of the study showed that despite positive assessments of the urban environment around them, they are ready to move to larger cities that provide more opportunities for self-realization and successful employment.